The prevalence of chronic postmastectomy pain syndrome in female breast cancer survivors. (5th August 2016) - Variawa, Muhammed Luqmaan; Scribante, Juan; Perrie, Helen; Chetty, Sean
Abstract : Background: Breast cancer is one of the most common cancer diagnoses in women. Surgical treatment is indicated in most patients. Postmastectomy pain syndrome (PMPS) is a debilitating neuropathic pain syndrome that develops after breast surgery. A review of the literature revealed no studies determining the prevalence of PMPS conducted in South Africa. The current anecdotal perception is that the prevalence of PMPS in the African population is low. Objectives: The objectives of this study were to determine the prevalence of PMPS in adult female breast cancer patients following general anaesthesia without regional anaesthesia at the Chris Hani Baragwanath Academic Hospital (CHBAH), as well as the impact of various clinical and demographic variables on the prevalence of PMPS. Methods: The research design was a cross-sectional descriptive study. The validated DN4 pain questionnaire was used in this study. Results: The study included 92 patients. The prevalence of PMPS was found to be 38.04% ( n = 35). The average duration that patients experienced neuropathic pain symptoms was 12.22 months (range 3–39 months). The average age of patients interviewed was 58.54 years (range 30–90 years). There was no statistically significant difference between age group and PMPS ( p = 0.47). The study also showed that no statistically significant association existed between pain experienced and adjuvant therapy administered. Conclusion: Even though surgical procedures are becoming less invasive, the prevalence of PMPS after treatment for breast cancer remains a clinically significant problem, comparable to international literature. This necessitates the development of more effective prevention and treatment strategies to improve patients' quality of life.